Малые храмы-часовни Херсонеса - Рыжов, С. Г. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryS. Ryzhov Small temples of ChersonesusThe architectural appearance of Chersonesus was determined not only by political realia but also by ideology and religious outlook. In the X-XIII centuries a new element appears side with urban estate. It was a chapel, that was used as a family church, family grave and the place where diptychs were kept. 5 chapels functionated in the northen part of Chersonesus. This type of chapel could be found in almost all the residential blocks, that was probably connected with falling numbers of public church. From the research of a temple in "10 B" block of the Northern region, its size, peculiarity of construction, signs of plaster work and paintings on its apse, remained plinth and 4 graves we can deduce, that the temples were up to all the requiremts of Christian worship.Appearance of temples and small churches became possible only after strengthening of Christianity as an official religion and the main outlook of Chersonesus citizens.